Think-Pair-Share (TPS) Model: A Pathway to Enhancing Mathematics Achievement and Self-Efficacy in Elementary School Students - NST, Tasa Amanda; Habibie, Zulqoidi R; Sundahry, Sundahry (Prima: Jurnal Pendidikan Matematika, 2025)
This study examines the effect of the Think Pair Share (TPS) learning model on mathematics learning outcomes and students’ self-efficacy, as well as the relationship between the two variables among fifth-grade students at SDN 109/II Manggis. Using a quantitative experimental method with a pretest–posttest control group design, the experimental class was taught using TPS, while the control class received conventional instruction. Data were collected through a mathematics test and a self-efficacy questionnaire, analyzed with SPSS 25 using the Wilcoxon Signed Rank Test, Paired Sample t-Test, and Pearson Product Moment correlation. Results indicated that TPS significantly improved mathematics learning outcomes and self-efficacy. A strong positive correlation (r = 0.656, p < 0.05) was found between self-efficacy and learning outcomes. TPS is thus recommended as an effective alternative for elementary mathematics instruction, enhancing both academic achievement and students’ confidence.